Foto Sudah Mati? Pergeseran Paradigma dan Pemaknaan Kebenaran dalam Fotografi - Setiawan, F. X. Rudi (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2013)
Critique of photography came into view from within. The advance of the technology of photography always opens the possibility that a photograph can be manipulated, especially from the time of the invention of digital technology. The implication is that subjectivity and intentionality are interwoven with the photographical processes. Photographical truth in journalism cannot rely on the singular and absolute ‘mechanical’ truth, but on its ‘contextualisation’ that cannot presuppose intersubjective agreements in producing common measures. This paper aims at affirming the position that one can make sense of the objectivity of journalism photography only in the context of intersubjective consensus. The distinctiveness of a photograph compared to other visual and expressive media lies in the process and the procedure of the making. The problem is a photograph does not tell how it is made. The causal relation in the photographical process gives the epistemological status of a photograph. Photography today cannot be understood within the causality framework that is too instrumentalistic and impersonal. Photography becomes more and more intentional, like painting and furthermore text. Major themes like causality, correspondence, accurateness, and objectivity are contested. However, photography is still powerful not only by virtue of its descriptive-explanatory role in imaging the reality in a realistic way, but also on account of its metaphorical aspect. “Photography is dead” only if it is considered as a representation of the reality. Photography will not die if it is seen poetically as our interpretation of reality.